2020
DOI: 10.23917/humaniora.v21i2.9591
|View full text |Cite
|
Sign up to set email alerts
|

The Ideology of Donald Trump on His Speech at the Israel Museum: Fairclough’s Three Models of Cda

Abstract: This research investigated the ideology of Donald Trump on his speech at the Israel museum. This research focused on analysing illocutionary acts to discover the ideology of Trump on his speech. This research used qualitative approach. The design of this research is Critical Discourse Analysis (CDA). This research used Fairclough’s three models of CDA, namely: textual analysis, discursive practice and social practice The result that showed there were five types of illocutionary acts expressed, those are repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, his local political considerations on a rational and realistic approach to the external policy were uncovered. Faiz, Chojimah, and Khasanah (2020) analyzed the illocutionary acts and the ideology of Trump in his speech about Jerusalem. They used Fairclough"s three models of CDA and found that there are five types of illocutionary acts, with representatives being the most frequently used by Trump.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
“…Furthermore, his local political considerations on a rational and realistic approach to the external policy were uncovered. Faiz, Chojimah, and Khasanah (2020) analyzed the illocutionary acts and the ideology of Trump in his speech about Jerusalem. They used Fairclough"s three models of CDA and found that there are five types of illocutionary acts, with representatives being the most frequently used by Trump.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%